Experimental evidence on the effects of innovation contests - Julia Brueggemann; Lukas Meub (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
Economic research on innovation has long discussed which policy instruments best foster innovativeness in individuals and organizations. One of the instruments easily accessible to policy-makers is innovation contests; however, there is ambiguous empirical evidence concerning how such contests should be designed. Our experimental study provides evidence by analyzing the effects of two different innovation contests on subjects innovativeness: a prize for the aggregate innovativeness and a prize for the best innovation. We implement a creative real effort task simulating a sequential innovation process, whereby subjects determine royalty fees for their created products, which also serve as a measure of cooperation. We find that both contest conditions reduce the willingness to cooperate between subjects compared to a benchmark condition without an innovation contest. However, the total innovation activity is not influenced by introducing innovation contest schemes. From a policy perspective, the implementation of state-subsidized innovation contests in addition to the existing intellectual property rights system should be questioned.
Keywords: C91; D89; O31; 330; innovation prizes; competition; laboratory experiment; real effort task; creativity; innovation policy